1968-1978: the student movement as a new character? - Almada, Pablo Emanuel Romero (Laboratório Editorial Faculdade de Ciências e Letras, 2021)
The article analyzes the starting over of the mobilizations by the student movement in the 1970s, particularly on the National Union of Students (UNE) institutional reconstruction, its preparatory events, and repression suffered, such as the invasion of PUC-SP in 1977. Firstly, we discuss Eder Sader's concept of 'new characters,' the relevance of analyzing the student's reorganization process in this theoretical matrix, given the persecution and silencing of their actions. Secondly, through the methodology of historical sociology and document analysis, the article explores, especially in the city of São Paulo, the relationship between the student movement and the progressive sectors of the Catholic Church, especially in the figure of D. Paulo Evaristo Arns. Finally, the article concludes that this approach was fundamental for understanding the student's organizational process and the mobilizations in favor of human rights for a democratic society.